Adolescent sun protection at secondary school athletic sporting events - a misnomer - Bronwen M. McNoe; Anthony I. Reeder (Elsevier, 2016)
Abstract Objective: To observe the sun‐protective practices of students and staff and related aspects of the physical environment at secondary school athletics days. Methods: This observational study of 1,225 students and 215 adult supervisors examined the use of sun‐protective items (hats, clothing coverage, sunglasses), sunscreen provision and shade. Results: Sun‐protective behaviour was poor with only 3% of students and 25% of adult supervisors wearing a sun‐protective hat. Shade was not available to most students, either as competitors or while waiting to compete. Sunscreen provision was 50%. Conclusion: Portable shade for students waiting to compete should be available at competitive events. Students should be encouraged to wear sun‐protective hats and clothing while not competing and SPF30+ broad‐spectrum sunscreen should always be provided. Guidelines for adult supervisors should be developed so they role model appropriate sun protection.